The effect of provision of cherry leaves booked water on the reduction of blood sugar levels in type 2 diabetes mellitus patients - Rumiris Simatupang (Science Midwifery, 2023)
DM is a chronic condition in which there is an increase in glucose levels in the blood because the body cannot produce or produce insulin or the body cannot use insulin effectively. Based on data from the International Diabetes Federation (IDF) Organization, it is estimated that there are 463 million people aged 20-79 years in the world suffering from diabetes mellitus (DM) in 2019 or equivalent to 9.3 of the total population aged 20-79 years. According to the International Diabetes Federation (2019), there are 10.7 million DM sufferers in Indonesia. Cherry leaves can be used as a scientific alternative to non-pharmacological therapy with cherry leaf decoction to reduce blood glucose levels, because this plant contains flavonoid compounds, tannins, saponins, and alkaloids that can lower blood sugar levels. The purpose of this study was to determine the effect of boiled water on cherry leaves to reduce blood sugar levels of people with type 2 Diabetes Mellitus in the working area of ​​the Central Tapanuli Sarudik Health Center. In this study, people who suffer from type 2 DM in the working area of ​​the Puskesmas Sarudik Tapanuli Tengah with purposive sampling technique as many as 30 people. h DM patients where the p value is 0.000 <0.05 with a t value of 6.723 with an average value before and after being given Decoction of Cherry Leaf Water which means that there is a decrease in blood sugar levels of DM patients after being given boiled water of cherry leaves.